Recurrent Dacryostenosis as Initial Presentation of Sarcoidosis. (9th September 2012) - Blouin, Marie Julie; Black, Daniel O.; Fradet, Gaetan
Abstract : Sarcoidosis is a multisystem granulomatous disease with an unknown etiology. It most commonly affects young and middle-aged females. It can affect any organ, but mostly lung, skin, and eyes. Up to half of patients are asymptomatic and the disease is often detected incidentally on abnormal chest radiography. We report the case of a 31-year-old male with bilateral recurrent dacryostenosis. The nasolacrimal obstruction was the initial manifestation of systemic sarcoidosis.